The salivary levels of leptin and interleukin-6 as potential inflammatory markers in children obesity. - Corina Pîrsean; Cătălina Neguț; Raluca-Ioana Stefan-van Staden; Cristina Elena Dinu-Pirvu; Petru Armean; Denisa Ioana Udeanu (PLoS ONE, 2019)
Background Obesity among children is an alarming issue due to an increased incidence over the last years with devastating physiological and psychological consequences. Current available medical diagnostic tools use invasive methods to evaluate and monitor the lipid profile, glycaemia or liver status for determining the overweight/ obesity complications. The standard methods proposed for the assay of IL6 and leptin from saliva cannot detect these two biomarkers in children saliva; the levels of IL6 and leptin in children's saliva are lower than the limit of determination of the standard methods. Therefore, we proposed a method based on utilization of stochastic sensors, able to simultaneously perform a qualitative and quantitative determination of these two biomarkers within minutes, in the range able to cover healthy and obese children. Methods Children from the urban area monitored for annual standard analyses and health status assessment at National Institute of Endocrinology C.I. Parhon within University of Medicine and Pharmacy "Carol Davila", Bucharest, Romania were included in the study. In the same day, for all participants of the study, blood analyses were performed and saliva samples were collected for the determination of the IL-6 and leptin levels. Findings/ results The children diagnosed with overweight/ obesity presented not significantly different blood lipid profile and glycaemia comparing to the control group. Only few cases of the children presented high levels of cholesterol, low level of HDL-cholesterol, a slightly increased level of triglycerides and transaminases. No correlation with the body mass index could be established with the blood analyses results. In case of the overweight/obese children, the salivary level of the proinflammatory citokynes IL-6 (41ng/mL±21) and leptin (40.4ng/mL±28.8), were significantly increased comparing to normal weight children (IL-6 8.1±4.6, leptin 9.58±3.1). Moreover, the saliva level of the IL-6 was positively correlated with the body mass index. Salivary leptin level was highly variable in case of obese children, 6 patients presenting similar levels with the control group. Conclusions Increased levels of salivary IL-6 and leptin sustain a systemic inflammation status despite normal range of standard blood analyses. The results were positively correlated in case of IL-6 with the body mass index the general accepted method used for the assessment of the obesity or overweight degree The determination of these markers in saliva samples by a stochastic method proved the utility within the medical examination for a better evaluation of the health status in obesity. The method has some advantages like: easy collection of the biological sample, fast determination of low concentrations and could be promising in case of no associated oral cavity infections or inflammations which could interfere the results.